Scattering approach to Anderson localization - Ossipov, A. (American Physical Society, 2018)
We develop a novel approach to the Anderson localization problem in a d-dimensional disordered sample of dimension L×Md−1. Attaching a perfect lead with the cross section Md−1 to one side of the sample, we derive evolution equations for the scattering matrix and the Wigner-Smith time delay matrix as a function of L. Using them one obtains the Fokker-Planck equation for the distribution of the proper delay times and the evolution equation for their density at weak disorder. The latter can be mapped onto a nonlinear partial differential equation of the Burgers type, for which a complete analytical solution for arbitrary L is constructed. Analyzing the solution for a cubic sample with M=L in the limit L→∞, we find that for d2 to the metallic fixed point, and provide explicit results for the density of the delay times in these two limits.